2010
DOI: 10.3390/ijms11052067
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and Anti-Inflammatory Activities of the Ethanol Extract of Annona muricata L. Leaves in Animal Models

Abstract: Antinociceptive and anti-inflammatory activities of the ethanol extract from Annona muricata L. leaves were investigated in animal models. The extract delivered per oral route (p.o.) reduced the number of abdominal contortions by 14.42% (at a dose of 200 mg/kg) and 41.41% (400 mg/kg). Doses of 200 and 400 mg/kg (p.o) inhibited both phases of the time paw licking: first phase (23.67% and 45.02%) and the second phase (30.09% and 50.02%), respectively. The extract (p.o.) increased the reaction time on a hot plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(117 citation statements)
references
References 36 publications
4
101
0
12
Order By: Relevance
“…In this study, experimental results show that the ethanolic extract of AML performs as an anti-inflammatory agent in mice and rats in both acute and chronic inflammation models. Priorly, AML has been reported on its anti-inflammatory and antinociceptive effects on different animal models (De Sousa et al, 2010;Roslida et al, 2010;. Thus, the current findings have strongly supported the claim that AML possesses anti-inflammatory effect as well as anti-arthritic activity based on the data from the current results.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this study, experimental results show that the ethanolic extract of AML performs as an anti-inflammatory agent in mice and rats in both acute and chronic inflammation models. Priorly, AML has been reported on its anti-inflammatory and antinociceptive effects on different animal models (De Sousa et al, 2010;Roslida et al, 2010;. Thus, the current findings have strongly supported the claim that AML possesses anti-inflammatory effect as well as anti-arthritic activity based on the data from the current results.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, A. muricata leaf extracts have antioxidant (Baskar et al, 2007) and molluscicidal properties (Santos & Sant'Ana, 2001;Luna et al, 2006). Although there are a few studies have been reported on the anti-inflammatory actions of the plant's leaves (Roslida et al, 2010;De Sousa et al, 2010), but none of them has yet reported the effect of the plant's leaves in the chronic inflammation. Various non-steroidal anti-inflammatory drugs (NSAID) are widely used clinically for inflammatory diseases as well as rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…muricata is found widely in the West Indies, South and Central America, tropical West Africa, and Asia. In the West Indies, various parts of the plant, including the leaves, bark and roots have been used to treat disease conditions such as diabetes (Adeyemi et al, 2008(Adeyemi et al, , 2010 A. muricata include its anticancer (Oberlies et al, 1997;Liaw et al, 2002), antibacterial and antifungal (Takahashi et al, 2006) actions, as well as, its antinociceptive and anti-inflammatory effects (de Sousa et al, 2010). Phytochemical screening of the leaves of A. muricata has shown it to consist of alkaloids such as reticuline, coreximine, coclarine and anomurine (Leboeuf et al, 1981(Leboeuf et al, , 1982, annomuricin E, annomuricin C, muricatocin C, gigantetronenin and muricapentocin with antioxidant and antitumor properties (Wu et al, 1995;Kim et al, 1998;Luna et al, 2006;Baskar et al, 2007), as well as, essential oils such as β-caryophyllene, δ-cadinene, epi-α-cadinol and α-cadinol (Pelissler et al, 1994;Kossouoh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports on Annona muricata reveal it possesses anti-oxidant effect Baskar [10] anti-proliferative effect [11,12] and anti-trypanosomal effects [13], anti-bacterial effect [14,15], anti-hepatotoxic activity [16,17], wound healing activity [18]. The antinociceptive and anti-inflammatory effect of the ethanol extract of the plant in animal models has also been reported [19][20][21]. Despite studies on the anti-inflammatory activity of Annona muricata leaves, there is little or no empirical evidence on its anti-inflammatory mechanisms of action.…”
Section: Determination Of the Effect Of The Extract On Phospholipase mentioning
confidence: 99%